2019
DOI: 10.1097/md.0000000000014288
|View full text |Cite
|
Sign up to set email alerts
|

Association of transcription factor 7-like 2 (TCF7L2) gene polymorphism with type 2 diabetes mellitus in Chinese Korean ethnicity population

Abstract: Presently, data on the type 2 diabetes mellitus (T2DM) in Chinese Korean ethnicity are very scarce. This study aimed to explore the relationship between the transcription factor 7-like 2 (TCF7L2) and T2DM in Chinese Korean ethnicity population. This case-control study involved 43 T2DM Chinese Korean ethnicity patients (T2DM group) and 43 healthy Chinese Korean ethnicity normoglycemic subjects as controls (Control group). All included participants aged from 40 to 75 years old. Clinical and biological data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…In particular, in the present study of the Russian population, we revealed that the T allele of this polymorphism is more common in the participants with prediabetes, T2D and obesity. The same results were shown in a number of other studies, which demonstrate the association of TCF7L2 rs7903146 with T2D in across many ethnic populations [21][22][23]. However, there appears to be no significant association between the T allele of TCF7L2 rs7903146 and T2D risk in Chinese population [24].…”
Section: Discussionsupporting
confidence: 82%
“…In particular, in the present study of the Russian population, we revealed that the T allele of this polymorphism is more common in the participants with prediabetes, T2D and obesity. The same results were shown in a number of other studies, which demonstrate the association of TCF7L2 rs7903146 with T2D in across many ethnic populations [21][22][23]. However, there appears to be no significant association between the T allele of TCF7L2 rs7903146 and T2D risk in Chinese population [24].…”
Section: Discussionsupporting
confidence: 82%
“…The transcription factor 7-like 2 ( TCF7L2 ) gene is located at human chromosome 10q25.3, 215.9 kb long, with 17 identified extrons. Previous studies have showed the relationship between TCF7L2 gene and common diseases such as type 2 diabetes mellitus (T2DM) [ 9 ], diabetic nephropathy (DN) [ 10 ], nonalcoholic fatty liver [ 11 ] and some cancers [ 12 , 13 ]. The relationship between single nucleotide polymorphism (SNPs) of TCF7L2 gene and BC risk was also reported in German [ 14 ], Hispanic [ 15 ], United States [ 16 , 17 ] and Chinese population [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the present study of the Russian population, we revealed that the T allele of this polymorphism is more common in the participants with prediabetes, T2D and obesity. The same results were shown in a number of other studies, which demonstrate the association of rs7903146 TCF7L2 with T2D in across many ethnic populations [19][20][21]. However, there appears to be no signi cant association between the T allele of rs7903146 TCF7L2 and T2D risk in Chinese population [22].…”
Section: Discussionsupporting
confidence: 82%